Use of English and code-mixing in TV commercials in Lithuania - Vaicekauskienė, Loreta; Šmitaitė, Reda (Kalbotyra, 2010)
The paper focuses on the problem of language domain loss and sets out to examine the relationship between Lithuanian and English in TV commercials in Lithuania. The aim of the research is to determine the spread of English, together with the functions of English elements in the commercials and code-mixing. The data consists of a corpus of TV commercials recorded in 2003 and in 2009; in total, more than 1200 commercials, broadcasted during the most popular TV programs in one week each year. The analysis has shown that TV advertising as a domain of Lithuanian language use is not being lost and the situation hasn’t changed over the years. There are almost no only English commercials. Most of the commercials are a mix of Lithuanian and English codes, while English is mostly used in the product names. There are few English slogans and not much other information in English in the corpus. It turned out that there might be a special strategy for the localization of commercials in Lithuania. The oral form of the commercials is more Lithuanized than thewritten form. The slogans and the product names are presented in translation or explained in Lithuanian. At the same time, the written part of the commercials can have more information in English. Some English insertions most likely have a symbolic function to make an impression that the product advertised is valuable or modern. The use of English in commercials may have the purpose of communicating prestige and especially targeting at an audience with a high social status or young people.